Pengaruh Aplikasi Kompos Tandan Kosong Kelapa Sawit (Elaeis guineensis Jacq) Terhadap Pertumbuhan Vegetatif Bibit di Main Nursery - Walmadri Walmadri; Muhammad Irfan Abdillah; Arief Setiawan Sutanto; Fastabiqul Khairad (Mahesa Research Institute, 2023)
This research was carried out in the practice garden and Laboratory of the Indonesian Palm Oil Institute (ITSI) Medan. It will be carried out from March to June 2022 to get the growth and development of oil palm seedlings by applying empty palm fruit bunch compost as the use of organic fertilizer during the nursery period. This study used a Non-Factorial Randomized Block Design (RBD) with one factor studied, namely variations in the application of compost to oil palm seedlings. Parameters observed were plant height, stem diameter, number of leaves, root length, root volume, root fresh weight, shoot wet weight, root dry weight, shoot dry weight. The data obtained was analyzed statistically by Analysis Of Variance (ANOVA). Based on the results of observations and analysis of variance, it was shown that the application of empty palm fruit bunch compost had a significant effect on shoot wet weight and had a significant effect on shoot dry weight and had a significant effect on stem diameter growth at 16 WAP observations, and had no significant effect on plant height, number leaves, root length, root volume, root wet weight, root dry weight.